Heart rate variability and experimentally induced pain in healthy adults: a systematic review - Koenig, Julian; Jarczok, Marc N.; Ellis, Robert J.; Hillecke, Thomas; Thayer, Julian F. (European journal of pain, 2014)
Background Reactivity of the autonomic nervous system to experimental pain stimuli has been extensively studied using measures of heart rate and blood pressure. Heart rate variability (HRV) attempts to tease out the relative contributions of sympathetic and parasympathetic activity in the autonomic control of the heart and may therefore be more appropriate to investigate autonomic response to short-term nociceptive stimulation in detail. The current evidence on HRV and experimentally induced pain has not yet been synthesized within a systematic review. Method English articles indexed in PubMed, EMBASE, Psyndex, PsycINFO, CINAHL and the Cochrane Library were reviewed for eligibility under pre-specified inclusion criteria. Studies were included when they reported empirical work on autonomic response (specifically, HRV) to experimentally induced pain in healthy adults. The method of pain induction, the methodological features of HRV analysis (time domain and frequency domain measures), as well as pain and HRV-related findings were derived from the studies. Results The search revealed a total of 20 publications eligible for inclusion. Key results demonstrate an increase in sympathetic-baroreflex activity and a decrease in vagal-parasympathetic activity as reflected by changes in frequency domain measures of HRV. Conclusion HRV has several advantages compared to other measures of autonomic reactivity in studies investigating physiological response to nociceptive stimulation. Future studies should focus on comparisons between different methods of pain induction, interindividual variability in pain sensitivity by baseline autonomic activity, and the implications of both on the use of HRV within routine clinical evaluations.
First published: 06 August 2013
Gesehen am 09.12.2021